2018
DOI: 10.1016/j.jconrel.2018.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced uptake in 2D- and 3D- lung cancer cell models of redox responsive PEGylated nanoparticles with sensitivity to reducing extra- and intracellular environments

Abstract: In the treatment of lung cancer, there is an urgent need of innovative medicines to optimize pharmacological responses of conventional chemotherapeutics while attenuating side effects. Here, we have exploited some relatively unexplored subtle differences in reduction potential, associated with cancer cell microenvironments in addition to the well-known changes in intracellular redox environment. We report the synthesis and application of novel redox-responsive PLGA (poly(lactic-co-glycolic acid)) -PEG (polyeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 45 publications
5
57
0
Order By: Relevance
“…[73] Each material was incubated in GSH in PBS at 37°C and measured at 1, 24, and 48 h to assess any changes in size. [74] The linear, star and hyperbranched structures showed a decrease in diameter over time as expected (Figure 1D,E) due to disassembly into their smaller linear fragments, however there was no significant change in the diameter of the core-crosslinked micelles during the experiment. As the micelles were core-crosslinked in situ during the polymerization process, it is likely that the disulfides are embedded deep within the hydrophobic core and thus are not very accessible.…”
Section: In Vitro Stability and Controlled Degradation Of Phpmassupporting
confidence: 77%
“…[73] Each material was incubated in GSH in PBS at 37°C and measured at 1, 24, and 48 h to assess any changes in size. [74] The linear, star and hyperbranched structures showed a decrease in diameter over time as expected (Figure 1D,E) due to disassembly into their smaller linear fragments, however there was no significant change in the diameter of the core-crosslinked micelles during the experiment. As the micelles were core-crosslinked in situ during the polymerization process, it is likely that the disulfides are embedded deep within the hydrophobic core and thus are not very accessible.…”
Section: In Vitro Stability and Controlled Degradation Of Phpmassupporting
confidence: 77%
“…However, when exposing the already formed spheroids for 24 h, NPs were seen only to a depth of 20 µm [26]. Cell types, cell densities, physicochemical characteristics of the NPs (including size distribution) and ion release may influence the penetration inside the spheroid [73][74][75][76][77].…”
Section: Discussionmentioning
confidence: 99%
“…The cell uptake efficiency of redox-responsive NPs on 3D cell culture models of lung cancer was higher than that of nonredox-responsive NPs, and the extracellular release of PEG fringe could promote the internalization of NPs. 102 Redoxresponsive PTX-loaded PEG micelles were modified with ABD035, a peptide with albumin-binding domain, targeting overexpressing albumin-binding proteins such as secreted protein acidic and rich in cysteine (SPARC) and gp60. The cellular internalization results indicated that the accelerated transport rate was due to SPARC-and caveolin-1-mediated pathways and therefore improved therapeutic effects on representative drug resistance model: triple-negative breast cancer by increasing cellular internalization as well as drug distribution.…”
Section: Pegmentioning
confidence: 99%